Pengaruh Model Problem Based Learning Berbantuan Media Math Magic Card Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII SMPN 15 Mataram - Pratiwi Bunga Angkasa; Nurul Hikmah; Ulfa Lu'luilmaknun (Griya Journal of Mathematics Education and Application, 2025)
Problem solving ability is an important competence in learning mathematics, but the results of observations at SMPN 15 Mataram showed that the ability is still relatively low. This study aims to determine the effect of Problem Based Learning (PBL) model assisted by Math Magic Card media on the ability to solve math problems of grade VIII students of SMPN 15 Mataram academic year 2025/2026. The type of research used is quasi-experimental with posttest-only nonequivalent group design. The study population was all students of Class VIII, with a sample of two classes, namely Class VIII J as an experimental group that applies the PBL model assisted by Math Magic Card and Class VIII K as a control group that applies the conventional learning model. Data were collected through a test of problem-solving skills in the form of problem descriptions prepared based on Polya indicators. The test has been validated by an expert (validator) and declared valid for use in research. Based on the results of the normality test shows that the research data are normally distributed and homogeneity test results show that the variance between groups is homogeneous. Then an independent t-test was conducted to determine the difference in the average problem solving ability of experimental class and control class with the results of at 5% significance level so that there is a significant difference between the two groups. The results showed that the average value of the experimental class posttest of 64.12 higher than the control class which only reached 50.23. The effect size value of 0.60 indicates the moderate influence of the application of PBL assisted Math Magic Card on students ' math problem solving skills. Thus, it can be concluded that the use of PBL models with the help of Math Magic Card media has an effect on improving students ' mathematical problem solving skills.